Electron affinity of lead. (5th March 2019) - Bresteau, D; Drag, C; Blondel, C
Abstract: A beam of Pb − ions produced by a cesium sputtering ion source is photodetached in the presence of an electric field, inside a linear optical cavity. Amplification of the light flux by the resonant cavity makes it possible to record exploitable photoelectron interferograms, even though the Pb − current does not exceed a few pA. The laser wavenumber is set either just above the first 3 P1 fine-structure excited threshold of neutral Pb, or above the higher 3 P2 threshold. The photoelectron kinetic energy is deduced from the electron interferograms with a precision high enough to provide a new experimental value of the electron affinity of lead, 8 times more precise and slightly lower than the one measured in 2016: e A ( Pb ) = 287 714.9 ( 1.5 ) m − 1 or 0.356 721(2) eV, instead of 287 733(13) m −1 or 0.356 743(16) eV.